2016
DOI: 10.1371/journal.pone.0150935
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of an Interactive Web-Based Near Real-Time Forest Monitoring System

Abstract: This paper describes an interactive web-based near real-time (NRT) forest monitoring system using four levels of geographic information services: 1) the acquisition of continuous data streams from satellite and community-based monitoring using mobile devices, 2) NRT forest disturbance detection based on satellite time-series, 3) presentation of forest disturbance data through a web-based application and social media and 4) interaction of the satellite based disturbance alerts with the end-user communities to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 66 publications
(105 reference statements)
0
33
0
2
Order By: Relevance
“…Many recent studies exemplify the importance of concept and technology development to meet these future demands (Dhamodaran, Sachin, & Kumar, 2015;Meissen, Hardt, & Voisard, 2014;Pratihast et al, 2016;Slavkovikj, Verstockt, Van Hoecke, & Van de Walle, 2014;Westling, Brynielsson, & Gustavi, 2014).…”
Section: Analysis An D Discussionmentioning
confidence: 99%
“…Many recent studies exemplify the importance of concept and technology development to meet these future demands (Dhamodaran, Sachin, & Kumar, 2015;Meissen, Hardt, & Voisard, 2014;Pratihast et al, 2016;Slavkovikj, Verstockt, Van Hoecke, & Van de Walle, 2014;Westling, Brynielsson, & Gustavi, 2014).…”
Section: Analysis An D Discussionmentioning
confidence: 99%
“…Another key management tool is near real-time monitoring of ecosystem threats utilizing community-based monitoring, remotely-sensed data, or in-situ sensors. These systems enable PA managers with time-sensitive alerts on deforestation threats of fires and illegal extractives to strategically patrol protected areas and enable rapid response to prevent further ecosystem destruction (e.g., [74][75][76][77]). …”
Section: Protected Areasmentioning
confidence: 99%
“…ArcGIS provides software for spatial data processing (ArcGIS for Desktop), data storage system (Geodatabase), software for spatial data sharing (ArcGIS for Server), and a multi-purpose spatial data platform (Portal for ArcGIS) for data utilization. Geoserver is used to generate and publish web-based map service and web feature service, keyhole markup language, and all of the things necessary to the development of WebGIS application [7] [19]. The management process of ESDM One Map Indonesia is performed in two ways.…”
Section: Datamentioning
confidence: 99%
“…With the internet, the distribution process of a considerable number of data becomes more efficient compared to manual dissemination. In the development, GIS and WebGIS-based analyses are increasingly adopted for a variety of purposes, such as environment and resource analysis [11], [15], [18], [21], [26]; rainfall distribution analysis [3], mining analysis [16], [19]; monitoring activities [7], [22], [25]; disaster analysis [1], [4], [17], [28]; and urban planning [12], [13], [14], [27]. Stancovic et al [19] demonstrated the benefits of WebGIS system for the management of abandoned mining sites in Serbia.…”
Section: Gis Dan Web-gismentioning
confidence: 99%